LHRH-conjugated, PEGylated, poly-lactide-co-glycolide nanocapsules for targeted delivery of combinational chemotherapeutic drugs Docetaxel and Quercetin for prostate cancer - Shitole, Ajinkya A.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand; Baruah, Meghna; Garnaik, Baijayantimala; Koratkar, Santosh (Materials Science & Engineering C-Materials for Biological Applications, 2020)
One of the major challenges in effective cancer chemotherapy is the severe systemic cytotoxicities of anticancer drugs on healthy tissues. The present study reports chemically modified polymeric nanocapsules (NCs) encapsulating combination of chemotherapeutic drugs Docetaxel (DTX) and Quercetin (QU) for its active targeting to prostate cancer (PCa). The active targeting was achieved by conjugating Luteinizing-hormone-releasing hormone (LHRH) ligand to poly-lactide-co-glycolide (PLGA) using polyethylene glycol (PEG) as a spacer. The structure of the conjugates was characterized and confirmed using H-1 NMR and ATR-FTIR. The drug encapsulated NCs showed a homogenous size distribution with their size ranging between 120 and 150 nm, and exhibited a negative zeta potential in the range of - 20 to - 40 mV. The in vitro release studies highlighted the sustained drug release pattern from the respective NCs; while the PEG coating to polymeric NCs provided serum stability to the NCs. The in vitro biological evaluation of the NCs was conducted using PC-3 and LNCaP cell lines. The results of the cellular uptake studies showed a significantly higher untake of the LHRH targeted NCs, while the LHRH-targeted-PEGylated DTX: QU NCs exhibited higher caspase-3 activity. The cell viability assay results showed the enhanced cell inhibition activity of the combinatorial DTX: QU when compared to individual DTX. Further, higher cell cytotoxicity was achieved by LHRH-targeted DTX: QU NCs as compared to their free-form or non-targeted NCs. Finally, the results of in vivo tumor localization and in vivo antitumor activity studies complimented and upheld the in vitro results, demonstrating the beneficial role of PLGA-PEG-LHRH NCs encapsulating combination of DTX and QU in combating prostate cancer (PCa).
Keywords: Active targeting; Anticancer; Controlled release; EPR effect; Hydrophobic; Prostate

Unbiased phenotype-based screen identifies therapeutic agents selective for metastatic prostate cancer - Chung, Ivy; Zhou, Kun; Barrows, Courtney; Banyard, Jacqueline; Wilson, Arianne; Rummel, Nathan; Mizokami, Atsushi; Basu, Sudipta; Sengupta, Poulomi; Shaikh, Badaruddin; Sengupta, Shiladitya; Bielenberg, Diane R.; et al. (Frontiers in Oncology, 2021)
In American men, prostate cancer is the second leading cause of cancer-related death. Dissemination of prostate cancer cells to distant organs significantly worsens patients' prognosis, and currently there are no effective treatment options that can cure advanced-stage prostate cancer. In an effort to identify compounds selective for metastatic prostate cancer cells over benign prostate cancer cells or normal prostate epithelial cells, we applied a phenotype-based in vitro drug screening method utilizing multiple prostate cancer cell lines to test 1,120 different compounds from a commercial drug library. Top drug candidates were then examined in multiple mouse xenograft models including subcutaneous tumor growth, experimental lung metastasis, and experimental bone metastasis assays. A subset of compounds including fenbendazole, fluspirilene, clofazimine, niclosamide, and suloctidil showed preferential cytotoxicity and apoptosis towards metastatic prostate cancer cells in vitro and in vivo. The bioavailability of the most discerning agents, especially fenbendazole and albendazole, was improved by formulating as micelles or nanoparticles. The enhanced forms of fenbendazole and albendazole significantly prolonged survival in mice bearing metastases, and albendazole-treated mice displayed significantly longer median survival times than paclitaxel-treated mice. Importantly, these drugs effectively targeted taxane-resistant tumors and bone metastases - two common clinical conditions in patients with aggressive prostate cancer. In summary, we find that metastatic prostate tumor cells differ from benign prostate tumor cells in their sensitivity to certain drug classes. Taken together, our results strongly suggest that albendazole, an anthelmintic medication, may represent a potential adjuvant or neoadjuvant to standard therapy in the treatment of disseminated prostate cancer.
Keywords: bone; carcinoma; drug-screen; Metastasis; Prostate